A decade-long study on mortality in European larch (Larix decidua Mill.), Japanese larch (Larix kaempferi (Lamb.) Car.) and their hybrid - Naincy Sagar; Luc E. Pâques; Stéphane Chantepie (Annals of Forest Science)
Abstract Key Message This study, based on a clonal larch experiment under contrasting soil water conditions, showed that Japanese larch exhibited the highest drought-induced mortality, followed by the hybrid and European larch. Mortality was driven by low soil water availability, high temperature, and vapor pressure deficit in late spring, and was negatively correlated with growth, indicating potential for selecting genotypes that combine high growth with greater survival. Context Mortality induced by climate extremes, particularly by drought, has been of growing concern due to the increasing frequency, intensity, and duration of drought episodes. Predicting tree mortality is a complex and multifaceted issue that involves not only tree-specific traits but also the environment, making it more challenging. Aim We aimed to identify species-specific mortality induced by the interaction between drought and other environmental factors, as well as the relationship between mortality and growth performance. Method We estimated the variation in the probability of mortality of Larix decidua Mill., Larix kaempfer (Lamb.) Car. and their hybrid over ten years in two plots with contrasting soil water availability. Using logistic regression, we identified the environmental variables and time windows that best explained this variation under two watering treatments. Finally, we tested the association between radial growth and mortality. Results Mortality was negligible for all three taxa in the irrigated plot. In the non-irrigated plot, Japanese larch exhibited the highest mortality, European larch the lowest, and the hybrid an intermediate level. Maximum temperature and vapor pressure deficit in late spring explained the temporal dynamics of mortality. Mortality was associated with reduced radial growth and was negatively correlated with mean long-term growth performance. Conclusion The differential mortality response of the two species and their hybrid to drought can provide insights for breeding programs. Selection for combined growth and enhanced survival seems possible.